Bolečine v ledvenem delu hrbtenice pri športnikih - Kolar, Jure (Šport (Ljubljana), 2018)
Low back pain is a major worldwide health problem in different age groups as well as in sports population. The symptoms present a huge public health burden, thus preventive and rehabilitation play a crucial role. There is a still large knowledge gap between scientific evidence and current practice, with scarce evidence investigating the effect of various prehabilitation interventions on low back pain morbidity, especially in youth sport. This article summaries the epidemiological basis of low back pain and present an aetiological background of the condition, with updated evidence based on non-pharmacological therapies. Moreover, the article also evaluates adjunctive treatment options for reduction of low back pain.
Keywords: bolečine v križu; etiologija; ledvena hrbtenica; preventiva; športniki; zdravljenje